Sociodemographic and psychological risk factors for anxiety and depression: Findings from the Covid-19 Health and Adherence Research in Scotland (CHARIS) cross-sectional survey THIS ARTICLE HAS BEEN PEER REVIEWED AND IS NOW AVAILABLE HERE: https://link.springer.com/article/10.1007/s12529-021-09967-z - Gill Hubbard; Chantal den Daas; Marie Johnston; Diane Dixon (2020)
ABSTRACTBackground: Investigations about mental health report prevalence rates with fewer studies investigating psychological and social factors influencing mental health during the Covid-19 pandemic. The aims of the study were to: (1) identify sociodemographic groups of the adult population at risk of anxiety and depression, and (2) determine if the following social and psychological risk factors for poor mental health moderated these direct sociodemographic effects: loneliness, social support, risk perception, and illness representations. MethodsCross sectional nationally representative telephone survey in Scotland in June 2020. If available, validated instruments were used for example, Patient Health Questionnaire (PHQ-4) to measure anxiety and depression. Simple linear regressions followed by examination of moderation effect. Results1006 participants; median age 53 years, 61.4% female, 3.8% in the most deprived and 15.6% in the most affluent areas. Analyses show associations of anxiety and depression with sociodemographic (age, gender, deprivation), social (social support, social isolation, loneliness) and psychological factors (perceived threat and illness representations). Mental health was poorer in younger adults, women and people living in the most deprived areas. Age effects were exaggerated by loneliness and illness representations, gender effects by loneliness and illness representations, and deprivation effects by loneliness, social support, illness representations and perceived threat. In each case, the moderating variables amplified the detrimental effects of the sociodemographic factors.ConclusionsThese findings confirm the results of previous studies about associations between sociodemographics and adult mental health. Loneliness, lack of social support and thoughts about Covid-19 exaggerated these effects and offer pointers for pre-emptive action.